(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The spatial resolved emission spectrum of Ni atom in laser induced Ni plasma is measured in the wavelength region from 350nm to 600nm. The spatial evolution of the relative intensities and the Stark broadening of the 385.83nm emission spectrum lines are also obtained. It is shown that Stark broadening and intensity of the spectrum lines increases firstly to its maximum and then decreases along the direction of laser beam when the distance from the target surface is in the range from 0 to 2.5 mm. The maximum value of Stark broadening and relative intensity of the spectrum lines appear at 1.5 mm from the target surface.